1987
DOI: 10.1152/ajpregu.1987.252.1.r40
|View full text |Cite
|
Sign up to set email alerts
|

Na+-H+ exchange and Na+-dependent transport systems in streptozotocin diabetic rat kidneys

Abstract: The streptozotocin-induced diabetic rat was used to test the hypothesis that Na+-H+ exchange activity in the proximal tubule luminal membrane would be increased in association with renal hypertrophy, altered glomerular hemodynamics, enhanced filtered load and tubular reabsorption of Na+, and stimulated Na+ pump activity in the basolateral membrane, previously reported characteristics of this experimental animal model. Amiloride-sensitive H+ gradient-dependent Na+ uptake and Na+ gradient-dependent H+ flux were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…In order to understand these findings, it is important to discuss the known effects of diabetes mellitus and thyroparathyroidectomy on urinary acidification. In micropuncture and microperfusion experiments it has been demonstrated that proximal tubular Na + reabsorption is increased in diabetes mellitus (30,31) and that the proximal reabsorption rates of bicarbonate are stimulated (1); in the present study, since the urinary flow as well as the final body weight were unchanged, the lower FE Na + seen in DM reflects an increased tubular reabsorption of Na + rather than a decrease in the extracellular volume status. On the other hand, previous studies from this laboratory (32) have shown that the rates of bicarbonate reabsorption in the proximal tubule of TPTX rats were decreased to the same extent as in a model of intact rats, whose tubules were perfused with a solution containing EGTA, an agent that chelates calcium.…”
Section: Discussionsupporting
confidence: 43%
“…In order to understand these findings, it is important to discuss the known effects of diabetes mellitus and thyroparathyroidectomy on urinary acidification. In micropuncture and microperfusion experiments it has been demonstrated that proximal tubular Na + reabsorption is increased in diabetes mellitus (30,31) and that the proximal reabsorption rates of bicarbonate are stimulated (1); in the present study, since the urinary flow as well as the final body weight were unchanged, the lower FE Na + seen in DM reflects an increased tubular reabsorption of Na + rather than a decrease in the extracellular volume status. On the other hand, previous studies from this laboratory (32) have shown that the rates of bicarbonate reabsorption in the proximal tubule of TPTX rats were decreased to the same extent as in a model of intact rats, whose tubules were perfused with a solution containing EGTA, an agent that chelates calcium.…”
Section: Discussionsupporting
confidence: 43%
“…Many abnormalities of the diabetic state have previously been shown to be corrected by insulin therapy (7,8,38,39). It was therefore of interest to examine the effect of this therapy on the enhanced Na+-H+ exchange associated with diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, recent studies in renal proximal tubular brush-border membrane vesicles isolated from streptozotocininduced diabetic rats have demonstrated an increase in electroneutral amiloride-sensitive, Na'-H' exchange activity in these preparations compared to their control counterparts, which was partially corrected by insulin administration (7,8). Since this ubiquitous transporter(s) has been implicated in a number of diverse physiological processes, including cellular proliferation (reviewed in reference 9), these authors suggested that this enhanced Na'-H' exchange might underlie known complications of the diabetic state such as renal hypertrophy (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown perturbations in ion transport in both the periphery and the brain during diabetes (1)(2)(3). Though diabetes is a vascular disease, little is known regarding the effects of diabetes on the blood-brain barrier (BBB) or the blood-cerebrospinal fluid barrier (BCSFB).…”
mentioning
confidence: 99%